Role of Ca2+ on Triggering Tonoplast Action Potential in Intact Nitella flexilis - Kikuyama, Munehiro; Shimmen, Teruo (Oxford University Press, 1997)
Sensitive aequorin was microinjected into the cytoplasm of Nitella flexilis to study the role of Ca2+ in the generation of the tonoplast action potential. The temporal relation between the increase in cytoplasmic Ca2+ and the tonoplast action potential suggested that tonoplast action potential is triggered by an increase in cytoplasmic Ca2+. This is also supported by the fact that Mn2+, extracellularly applied, inhibited both the increase in cytoplasmic Ca2+ and the generation of the tonoplast action potential.